China’s Political Reforms in the Early 21st Century - Nguyen Xuan Сuong (Vestnik MGIMO-Universiteta)
Analyzing process of political reforms in the People's Republic of China, the author notes that within the first 20 years of reforms and openness of China economic growth wasn't followed by development of society, political reforms didn't keep up for economic, imperfection of political system constrained economic reforms and development. Owing to this fact the XVI congress of a CPC lifted policy to the level of "political culture" by analogy with "material culture" and "spiritual culture". In the first 20 anniversary of the XXI century with the purpose to finish "comprehensive creation of society "of small prosperity" China has to create "perfect system of socialist market economy", construct "harmonious socialist society". For achievement of these purposes political reforms in China have to provide "improvement of socialist democracy" and "the socialist constitutional state". In the first years of the XXI century they brought a number of significant achievements: political stability, peaceful alternation of generations of the power, essential increase of level of political democracy. The first stage of formation of the constitutional socialist state is passed, ability and level of the management from ruling party increased; party construction amplified. But also at the beginning of the second decade of the XXI century implementation of the legislation, democracy faces many calls, especially intensification of nationalism at the beginning of the century. The Chinese dream will mobilize grandiose powers of unity that China deepened reforms and openness, solved all the political problems, helped a CPC to increase the leading and imperious power. Implementation process of "The Chinese dream" also means aspiration to tops of economy, policy, military science, technologies in the world, to a taking them, reflecting process of formation of the new great power which will succeed the USA. Political reforms with the purpose to achieve "The Chinese dream" have to be connected with peaceful development, make a contribution to development and progress of mankind, successful development, joint with all neighboring countries, and differently China will repeat history of crash and decline of civilizations and great powers.